MODEL PENINGKATAN KINERJA GURU MELALUI KEPEMIMPINAN TRANSFORMASIONAL, SELFEFFICACY DAN PERILAKU KERJA INOVATIF - Abu Rahman Tolib (Jurnal Riset Bisnis Indonesia, 2015)
This research has to analyze and examine the influence of transformational leadership and selfefficacyto innovative work behavior. Inside that, this research also to analyze and examine theinfluence of transformational leadership, self-efficacy and innovative work behavior to teacherperformance. This research had done by using a survey questionnaire with a sample of 146 teachers.Taking sample by using technique of sensus method. To examine the hypothesis is using SEMwith PLS (Partial Least Squares) program application. Result demonstrates that transformationalleadership and self-efficacy has positive and significant effects to innovative work behavior. Inaddition, transformational leadership, self-efficacy and innovative work behavior has positive andsignificant effect to teachers performance. Thus in improving teachers performance, we can increasetransformational leadership, self-efficacy and innovative work behavior. In which, the teacher showstheir professional in teaching.Keywords: transformational leadership, self-efficacy, innovative work behavior and teachersperformance.